Quantifying Slope Stability and Landslide Susceptibility Through Rainfall-Induced Geotechnical Assessment - Nasir, Nur Fazielah; Mohamad, Habib M.; Haziq Rosly, Mohammad; Omar, Heryanti Awang; Hamansa, Harryanshah (Civil Engineering Journal, 2025)
Landslides are a major hazard to people and infrastructure, especially in areas with weak geology and high rainfall. This study examined soil properties and slope stability in Ranau (RNU) and Kota Belud (KB), Sabah. Soil tests showed that RNU had 2–21% clay with cohesion of 3.49–9.7 kPa, while KB soils contained 2–17% clay, more sand and gravel, and much lower cohesion of 0.5–1.1 kPa, indicating weaker strength and higher permeability. Rainfall data from 2013–2023, provided by the Malaysian Meteorological Department, were used to develop Intensity-Duration-Frequency (IDF) curves. Results showed that 1-hour intensities increased from 0.92 mm/hr at ARI-2 to 2.18 mm/hr at ARI-100, reflecting the variation of extreme rainfall. Slope stability was analyzed using GeoStudio’s SEEP/W and SLOPE/W to simulate infiltration and compute the Factor of Safety (FOS). In RNU, FOS rose from 2.481 to 2.565 after 24 hours, showing stable slopes. In KB, FOS declined from 2.495 to 2.379 under ARI-100 rainfall, along with higher pore-water pressures. Both slopes remained above the safe limit of 1.50, but KB proved more vulnerable to long rainfall. Compared with earlier studies, this research introduces a decade-long dataset combined with numerical modelling to demonstrate the dynamic response of tropical slopes. The findings provide practical contributions to slope design, drainage management, and disaster risk reduction in regions experiencing similar climatic and geological conditions.